Comprehensive Comparative Effectiveness and Safety of First-Line β-Blocker Monotherapy in Hypertensive Patients: A Large-Scale Multicenter Observational Study. Issue 5 (29th March 2021) - Chan You, Seng; Krumholz, Harlan M.; Suchard, Marc A.; Schuemie, Martijn J.; Hripcsak, George; Chen, RuiJun; Shea, Steven; Duke, Jon; Pratt, Nicole; Reich, Christian G.; Madigan, David; Ryan, Patrick B.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Evidence for the effectiveness and safety of the third-generation β-blockers other than atenolol in hypertension remains scarce. We assessed the effectiveness and safety of β-blockers as first-line treatment for hypertension using 3 databases in the United States: 2 administrative claims databases and 1 electronic health record–based database from 2001 to 2018. In each database, comparative effectiveness of β-blockers for the risks of acute myocardial infarction, stroke, and hospitalization for heart failure was assessed, using large-scale propensity adjustment and empirical calibration. Estimates were combined across databases using random-effects meta-analyses. Overall, 118 133 and 267 891 patients initiated third-generation β-blockers (carvedilol and nebivolol) or atenolol, respectively. The pooled hazard ratios (HRs) of acute myocardial infarction, stroke, hospitalization for heart failure, and most metabolic complications were not different between the third-generation β-blockers versus atenolol after propensity score matching and empirical calibration (HR, 1.07 [95% CI, 0.74–1.55] for acute myocardial infarction; HR, 1.06 [95% CI, 0.87–1.31] for stroke; HR, 1.46 [95% CI, 0.99–2.24] for hospitalized heart failure). Third-generation β-blockers were associated with significantly higher risk of stroke than ACE (angiotensin-converting enzyme) inhibitors (HR, 1.29 [95% CI, 1.03–1.72]) and thiazide diuretics (HR, 1.56 [95% CI, 1.17–2.20]). In conclusion, this study found many patients with first-line β-blocker monotherapy for hypertension and no statistically significant differences in the effectiveness and safety comparing atenolol with third-generation β-blockers. Patients on third-generation β-blockers had a higher risk of stroke than those on ACE inhibitors and thiazide diuretics.